Modular, hollow culms of rain-forest bamboos explain their persistence across a wide range of light environments. (6th March 2018) - Fujinuma, Junichi; Potts, Matthew D.; Kassim, Abd Rahman; Harrison, Rhett D.; Razak O., Abd; Kohyama, Takashi S.
Abstract: Tropical bamboos persist in a wide range of light conditions and quickly respond to changes in light availability. However, the mechanisms underpinning this ability remain unknown. In order to test the hypothesis that the modular and hollow culm architecture of bamboos explains their performance in a wide range of light environments, we determined the allometric relationships of two dominant bamboo species of the upper hill dipterocarp forests of Malaysia, Gigantochloa ligulata (n = 29) and Schizostachyum grande (n = 25), via destructive sampling. We also monitored biomass turnover of bamboos and woody trees in 24 permanent plots (1.92 ha in total) over a one-year period. Compared with woody trees, bamboo culms attained 1.5 times the height and their clumps supported four times as much total leaf area at the same above-ground biomass. In addition, at a given height, bamboo clumps had six times larger crown projection area than trees while having a similar amount of total leaf area per unit of crown projection area. Finally, bamboos' biomass turnover rate was three times higher than trees, and G. ligulata increased its specific rate of biomass increase after canopy disturbance, while trees decreased. We conclude that the unique architecture of bamboos allows them to persist under closed forest canopy light conditions and to respond to gap formation via high biomass turnover rate.